2009
DOI: 10.1210/jc.2008-1199
|View full text |Cite
|
Sign up to set email alerts
|

FTO Genotype Is Associated with Body Mass Index after the Age of Seven Years But Not with Energy Intake or Leisure-Time Physical Activity

Abstract: Our results suggest that the effect of the FTO genotype on BMI becomes evident only after age 7 yr. These results further suggest that the FTO gene is not directly associated with energy intake or physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
122
7
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(155 citation statements)
references
References 41 publications
21
122
7
5
Order By: Relevance
“…Consistent with this observation is evidence from the ALSPAC study using 3 day dietary records, where children (10-11years) carrying the risk allele for FTO ingested more energy and specifi cally more dietary fat than those not carrying the risk allele (Timpson et al, 2008). These fi ndings contrast with at least three studies which report no associations with energy intake in children (Hakanen et al, 2009;Okuda et al, 2011;Stutzmann et al, 2009) and to the observation in mice that FTO may modulate energy homeostasis through energy expenditure (Fischer et al, 2009;Speakman, 2010). However, several studies, including a large meta-analysis have recently shown that energy expenditure through activity appears to attenuate the genetic susceptibility to overweight and obesity from FTO in children Scott et al, 2010) and adults (Andreasen et al, 2008;Kilpelainen et al, 2011).…”
Section: Fat Mass and Obesity Associated Gene And Eating Behaviourmentioning
confidence: 64%
See 2 more Smart Citations
“…Consistent with this observation is evidence from the ALSPAC study using 3 day dietary records, where children (10-11years) carrying the risk allele for FTO ingested more energy and specifi cally more dietary fat than those not carrying the risk allele (Timpson et al, 2008). These fi ndings contrast with at least three studies which report no associations with energy intake in children (Hakanen et al, 2009;Okuda et al, 2011;Stutzmann et al, 2009) and to the observation in mice that FTO may modulate energy homeostasis through energy expenditure (Fischer et al, 2009;Speakman, 2010). However, several studies, including a large meta-analysis have recently shown that energy expenditure through activity appears to attenuate the genetic susceptibility to overweight and obesity from FTO in children Scott et al, 2010) and adults (Andreasen et al, 2008;Kilpelainen et al, 2011).…”
Section: Fat Mass and Obesity Associated Gene And Eating Behaviourmentioning
confidence: 64%
“…A temporal dip in the effect of FTO rs9939609 on BMI in children is proposed at the mid-pubertal age of around 13-14 years which may be linked to alterations in physiologic and endocrine factors that trigger puberty (Rutters et al, 2011). Current thinking is that there is no FTO association with foetal growth (Frayling et al, 2007;Hakanen et al, 2009). …”
Section: Fat Mass and Obesity Associated Gene -A Role In Common Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-population differences in allele frequencies and patterns of linkage disequilibrium may also contribute to heterogeneity of findings. Previous studies have found that the influence of FTO on adiposity phenotypes is apparent from as young as 7 years old 7,32 and that the strength of the association increases into early adolescence. 10 In the GENESIS cohort, we observed association neither between FTO genotype and adiposity, which is in line with previous findings reporting no association of FTO genotype and childhood BMI in 2-5-year-old children, 33 nor between FTO genotype and energy intake (Supplementary Table 4).…”
Section: Discussionmentioning
confidence: 96%
“…10 In contrast, reduced energy expenditure and physical activity were not associated with FTO genotypes. 7,8,10,11 Nevertheless, physical activity modified the degree of obesity achieved in the context of the risk allele of FTO. 12,13 These pathomechanisms in man differed from mice lacking the Fto gene.…”
Section: Introductionmentioning
confidence: 93%